Medical student’s perception on teaching-learning methods of pharmacology in a medical college - Sravanthi Mukku, Lakshmi; Alla, Jagadeesh; Rachamanti, Ramya (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To know the Medical student’s perception on teaching and learning methods of pharmacology in a medical college attached to tertiary care hospital. Methods: This is a questionnaire based study conducted in a medical college. A pre-validated, pre-designed questionnaire containing 22 points was given to 5th semester students to know their perception on teaching and learning methods. Results: Analysis was done on 150 medical students of a tertiary care hospital. Among them, 80 % wanted the faculty members to make more utilization of Audio-Visual aids for effective learning. 78.67 % students wanted to include case based learning in the curriculum and 86.67% wanted more of the clinical pharmacology to be introduced. A 28% wanted MCQs (Multiple Choice Questions) to be included in the assessment of academic performance. A 13.33% felt that the ideal teaching method for learning pharmacology was didactic lectures. A 65% thought ideal teaching/learning media for pharmacology was the combination of LCD (Liquid Crystal display) projector and blackboard. Conclusions: The study revealed the ideal teaching and learning methods in pharmacology for the betterment of students.